White blood count, D‐dimers, and ferritin levels as predictive factors of pulmonary embolism suspected upon admission in noncritically ill COVID‐19 patients: The French multicenter CLOTVID retrospective study. (24th May 2021) - Galland, Joris; Thoreau, Benjamin; Delrue, Maxime; Neuwirth, Marie; Stepanian, Alain; Chauvin, Anthony; Dellal, Azeddine; Nallet, Olivier; Roriz, Melanie; Devaux, Mathilde; London, Jonathan; Martin‐Lecamp, Gonzague; et al.
Abstract: Background: A high prevalence of pulmonary embolism (PE) has been described during COVID‐19. Our aim was to identify predictive factors of PE in non‐ICU hospitalized COVID‐19 patients. Methods: Data and outcomes were collected upon admission during a French multicenter retrospective study, including patients hospitalized for COVID‐19, with a CT pulmonary angiography (CTPA) performed in the emergency department for suspected PE. Predictive factors significantly associated with PE were identified through a multivariate regression model. Results: A total of 88 patients (median [IQR] age of 68 years [60‐78]) were analyzed. Based on CTPA, 47 (53.4%) patients were diagnosed with PE, and 41 were not. D‐dimer ≥3000 ng/mL (OR 8.2 [95% CI] 1.3‐74.2, sensitivity (Se) 0.84, specificity (Sp) 0.78, P = .03), white blood count (WBC) ≥12.0 G/L (29.5 [2.3‐1221.2], Se 0.47, Sp 0.92, P = .02), and ferritin ≥480 µg/L (17.0 [1.7‐553.3], Se 0.96, Sp 0.44, P = .03) were independently associated with the PE diagnosis. The presence of the double criterion D‐dimer ≥3000 ng/mL and WBC ≥12.0 G/L was greatly associated with PE (OR 21.4 [4.0‐397.9], P = .004). Conclusion: The white blood count, the D‐dimer and ferritin levels could be used as an indication for CTPA to confirm PE on admission in non‐ICU COVID‐19 patients.